Persistent and Transient Airborne MRSA Colonization of Piglets in a Newly Established Animal Model - Rosen, Kerstin; Roesler, Uwe; Merle, Roswitha; Friese, Anika (Frontiers in Microbiology, 2018)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) was firstly found in 2005 and is up to date widespread in animal husbandry reservoir – focusing on pig farming. The regular detectability of MRSA in the air of pigsties as well as in exhaust air of pig farms (mean count: 102 cfu/m3) poses the question whether an airborne spread and, therefore, a MRSA colonization of animals via the airborne route exists. To answer this question, we exposed three groups of nine MRSA negative tested piglets each to a defined airborne MRSA concentration (102 cfu/m3, 104 cfu/m3 and 106 cfu/m3) in our aerosol chamber for 24 hours. In the following observation period of 21 days, the MRSA status of the piglets was monitored by taking different swab samples (nasal, pharyngeal, skin, conjunctival and rectal swab). At the end of the experiment, we euthanized the piglets and investigated different tissues and organs for the spread of MRSA. The data of our study imply the presence of an airborne MRSA colonization route: the animals exposed to 106 cfu/m3 MRSA in the air were persistent colonized. The piglets exposed to an airborne MRSA concentration of 104 cfu/m3 were transient and the piglets exposed to an airborne MRSA concentration of 102 cfu/m3 were not colonized. Consequently, a colonization via the airborne route was proven.